2013
DOI: 10.1002/cncy.21278
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of atypical urine cytology progression to malignancy

Abstract: BACKGROUND:In urine cytology, the diagnosis of atypia is subjective and clinical management based on these results can be difficult to determine. In this study, the authors determined the percentage of atypical urine diagnoses that progressed to positive cytology or surgical pathology results over an 11-year period. METHODS: In a retrospective review of the authors' institution, 1320 atypical urine cytology diagnoses were identified in specimens from 851 patients obtained from January 2000 through December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 9 publications
6
60
1
1
Order By: Relevance
“…Furthermore, in specimens containing cytologic atypia, a definitive diagnosis of HGUC was made significantly more often on UW than on VU specimens. Messer et al found that the use of selective ureteral catheterization improved the sensitivity for diagnosing UTHGUC from 56 to 71% compared with bladder VU/catheterization specimens, which is consistent with a historical study by Zincke et al Muus Ubago et al compared upper tract washings to VU specimens and found that 3.3% of upper tract washings were atypical versus around 9% for both VU and bladder washing specimens. Of the atypical upper tract washing specimens, 6.1% progressed to LGUC and 20.7% progressed to HGUC versus 4.1 and 8.5% for VU specimens, and 5.8 and 9.3% for bladder washing specimens.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, in specimens containing cytologic atypia, a definitive diagnosis of HGUC was made significantly more often on UW than on VU specimens. Messer et al found that the use of selective ureteral catheterization improved the sensitivity for diagnosing UTHGUC from 56 to 71% compared with bladder VU/catheterization specimens, which is consistent with a historical study by Zincke et al Muus Ubago et al compared upper tract washings to VU specimens and found that 3.3% of upper tract washings were atypical versus around 9% for both VU and bladder washing specimens. Of the atypical upper tract washing specimens, 6.1% progressed to LGUC and 20.7% progressed to HGUC versus 4.1 and 8.5% for VU specimens, and 5.8 and 9.3% for bladder washing specimens.…”
Section: Discussionsupporting
confidence: 67%
“… Excludes Muus Ubago et al, , which did not report the total number of biopsies and the complete results of the biopsies; instead, they reported the combination of positive biopsies and cytologies (21% frequency) after the diagnosis of atypia. Also excludes VandenBussche et al, , which did not report the total number of cytologies performed, the complete results of the biopsies (the “future test set” was excluded), and only provided results for high‐grade cancer; also, their category of “atypical, cannot exclude high‐grade urothelial carcinoma” had 95% cancer yield on biopsy, much higher than any comparable published reports.…”
Section: Resultsmentioning
confidence: 99%
“…25 However, even in the setting of equivocal cytology, the usefulness of U-FISH testing may depend on the indication for urinary cytology (surveillance, hematuria or others), as some authors believe that, U-FISH testing is not indicated in patients with microscopic hematuria, even in patients with persistent atypical urinary cytology who have other risk factors for urothelial carcinoma (older age, significant tobacco history), because of increased cost and the potential for false-positive results, which may lead to unnecessary invasive procedures. 7 Although there is hope that the recently published Paris System of Reporting Urinary Cytology 64-66 will contribute to the standardization and reduction of the frequency of this diagnosis, as has been already suggested by recent studies, 67,68 there is still a need to identify markers that may useful to further stratify the risk of malignancy in patients with a diagnosis of AUC. 63 This is further complicated by the fact that, during our study period there were no agreed-upon criteria for this diagnosis on urinary tract cytologic specimens and the rates with which AUC diagnoses were made have varied widely among institutions.…”
Section: Discussionmentioning
confidence: 99%